Comparison of Local and Systemic DTPA Treatment Efficacy According to Actinide Physicochemical Properties Following Lung or Wound Contamination in the Rat - Griffiths, Nina M.; Van der Meeren, Anne; Grémy, Olivier (Frontiers in Pharmacology, 2021)
Purpose: In cases of occupational accidents in nuclear facilities or subsequent to terrorist activities, the most likely routes of internal contamination with alpha-particle emitting actinides, such as plutonium (Pu) and americium (Am), are by inhalation or following wounding. Following contamination, actinide transfer to the circulation and subsequent deposition in skeleton and liver depends primarily on the physicochemical nature of the compound. The treatment remit following internal contamination is to decrease actinide retention and in consequence potential health risks, both at the contamination site and in systemic retention organs as well as to promote elimination. The only approved drug for decorporation of Pu and Am is the metal chelator diethylenetriaminepentaacetic acid (DTPA). However, a limited efficacy of DTPA has been reported following contamination with insoluble actinides, irrespective of the contamination route. The objectives of this work are to evaluate the efficacy of prompt local and/or systemic DTPA treatment regimens following lung or wound contamination by actinides with differing solubility. The conclusions are drawn from retrospective analysis of experimental studies carried out over 10 years. Materials and Methods: Rat lungs or wounds were contaminated either with poorly soluble Mixed OXide (U, Pu O2) or more soluble forms of Pu (nitrate or citrate). DTPA treatment was administered promptly after contamination, locally to lungs by insufflation of a powder or inhalation of aerosolized solution or by injection directly into the wound site. Intravenous injections of DTPA were given either once or repeated in combination with the local treatment. Doses ranged from 1 to 30 µmol/kg. Animals were euthanized from day 7–21 and alpha activity levels were measured in urine, lungs, wound, bone and liver for determination of decorporation efficacy. Results: Different experiments confirmed that whatever the route of contamination, most of the activity is retained at the entry site after insoluble MOX contamination as compared with contamination with more soluble forms which results in very low activities reaching the systemic compartment and subsequent retention in bone and liver. Several DTPA treatment regimens were evaluated that had no significant effect on either lung or wound levels compared with untreated animals. In contrast, in all cases systemic retention (skeleton and liver) was reduced and urinary excretion were enhanced irrespective of the contamination route or DTPA treatment regimen. Conclusion: The present study demonstrates that despite limitation of retention in systemic organs, different DTPA protocols were ineffective in removing insoluble actinides deposited in lungs or wound site. For moderately soluble actinides, local or intravenous DTPA treatment reduced activity levels both at contamination and at systemic sites.